The Effect of Inquiry Learning on Students' Critical Thinking Ability on the Topics of Regulation System - Yuni, Helma; Ulfa, Syarifah Widya (Jurnal Pendidikan MIPA, 2022)
Inquiry learning strategies are a series of learning activities that emphasize the process of thinking critically to find and find for yourself the answer to a problem in question. This study aims to determine the influence of inquiry learning strategies on the critical thinking ability of class XI science students of MIA Al-washliyah Kedaisianam. This research is in the form of quantitative research with a Quasi-experimental approach. The head of this study is students of class XI MIA 1 and XI MIA 2 Madrasah Aliyah Al-washliyah Kedaisianam Batu Bara school year 2022/2023. The design of this study is The Non-Equivalent Pretest Control Group Design. Data on students' critical abilities were collected using questionnaires. For then the research results obtained from the Non-test questionnaire in the experimental class and control class.Then the data obtained in the critical thinking ability analysis test of students of the two research classes were declared normally distributed and homogeneous and for the hypothesis test showed that the calculation of 20.071 > ttabel 1.669, then it can be categorized as having an influence. And for a significant degree of < 0.05 where 0.000 < 0.05, then H0 is rejected and Ha is accepted and concluded there is an influence of inquiry learning strategies on students' critical thinking ability on regulatory system materials.Keywords: critical thinking, inquiry learning strategies, regulatory systems.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1048-1056